2022
DOI: 10.1007/s43538-022-00070-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of COVID-19 pandemic on biomedical waste management, the impact beyond infection

Abstract: Excessive population outbursts and associated xenobiotic interventions contribute overproduction of waste materials across the world. Among these waste materials biomedical wastes (BMW) make a significant contribution. The huge accumulation of BMW is not only meant for successive environmental pollution but increases health hazards by cross-contamination and reoccurrence of different fatal infections. The management of BMW gaining continuous attention to the scientific communities for their intriguing potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
(42 reference statements)
0
15
0
1
Order By: Relevance
“…These toxicants are carcinogenic and can be stored in fat cells. Once entering the food chain, they activate aryl hydrocarbon receptors in humans which in turn induces hormonal imbalance, immunological disorders and also harms the immune system ( Ilyas et al, 2020 ; Bhar et al, 2022 ). Various disinfection processes, using steam, microwave, autoclave, chemicals as well as on-site incineration, are currently in use for managing harmful COVID-19 medical wastes in developing countries.…”
Section: Strategies For the Management Of Covid-19-related Healthcare...mentioning
confidence: 99%
“…These toxicants are carcinogenic and can be stored in fat cells. Once entering the food chain, they activate aryl hydrocarbon receptors in humans which in turn induces hormonal imbalance, immunological disorders and also harms the immune system ( Ilyas et al, 2020 ; Bhar et al, 2022 ). Various disinfection processes, using steam, microwave, autoclave, chemicals as well as on-site incineration, are currently in use for managing harmful COVID-19 medical wastes in developing countries.…”
Section: Strategies For the Management Of Covid-19-related Healthcare...mentioning
confidence: 99%
“…The general consensus around waste and recycling management systems during and after the peak of the pandemic is that they have been negatively impacted [21,[34][35][36][37][38][39]. From a broad perspective, the amount of household (municipal) waste generated in the EU was 181.4 million tonnes in 2016, 186.1 million tonnes in 2018 (the start of the pandemic), and 195.9 million tonnes in 2020 (largely considered the peak of the pandemic) [29].…”
Section: Performance Of Recycling and Waste Management Systemsmentioning
confidence: 99%
“…Thus, using pure numbers and statistics to assess the performance of recycling and waste management systems is difficult; this makes reviews such as this much more important and relevant. Out of the 29 articles discussing medical waste, every study found that medical waste has increased due to the COVID-19 pandemic and that further actions need to be taken [19,21,22,35]. Additionally, out of the three sub-categories, there was more information about municipal waste (37 articles) compared to medical waste (29 articles) (refer to figure 3).…”
Section: Performance Of Recycling and Waste Management Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the negative effects that this pandemic has caused on the environment are related to the large increase in the production of municipal solid waste (MSW) and how improper handling of it would increase the likelihood of the virus spreading as well as cause it to contaminate regular municipal waste (Nabavi-Pelesaraei et al, 2022 ), in addition to the low recycling or treatment capacity that existed at the time of the pandemic (Mohamed et al, 2022 ). The COVID-19 pandemic changed the rules of waste management, since inadequate management practices, poor waste management, and inadequate final disposal can increase the susceptibility to the spread of the virus, standards for the disposal of medical waste have been developed by several environmental and public health groups, but it is highly challenging to execute these guidelines effectively in the public sectors of developing nations (Bhar et al, 2022 ), especially in those areas where waste disposal was already unsustainable even before the COVID-19 due to ineffective treatment methods, the capacity limitations of healthcare facilities, and insufficient waste disposal techniques (El-Ramady et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%